Beta 1,3-1,6 Glucans Produced by Two Novel Strains of Aureobasidium Pullulans Exert Immune and Metabolic Beneficial Effects in Healthy Middle-aged Japanese Men: Results of an Exploratory Randomized Control Study - Ikewaki, N.; Sonoda, T.; Kurosawa, G.; Iwasaki, M.; Devaprasad Dedeepiya, V.; Senthilkumar, R.; Preethy, S.; Abraham, S.J.K. (JAR life, 2023)
In this pilot study, we have evaluated the specific metabolic and immune-related benefits of the AFO-202 strain and N-163 strain of black yeast Aureobasidium pullulans-produced beta 1,3-1,6 glucan in healthy human subjects. Sixteen healthy Japanese male volunteers (aged 40 to 60 years) took part in this clinical trial. They were divided into four groups (n = 4 each): Group I consumed AFO-202 beta-glucan (2 sachets of 1 g each per day), IA for 35 days and IB for 21 days; Group II consumed a combination of AFO-202 beta-glucan (2 sachets of 1 g each) and N-163 beta-glucan (1 sachet of 15 g gel each per day), IIA for 35 days and IIB for 21 days. Decrease in HbA1C and glycated albumin (GA), significant increase of eosinophils and monocytes and marginal decrease in D-dimer levels, decrease in neutrophil-to-lymphocyte ratio (NLR), with an increase in the lymphocyte-to-CRP ratio (LCR) and leukocyte-to-CRP ratio (LeCR) was observed in Group I between pre- and post-treatment. Decrease in total and LDL cholesterol, a decrease of CD11b, serum ferritin, galectin-3 and fibrinogen were profound in Group II between pre- and post-treatment. However, there was no statistically significant difference between day 21 and day 35 among the groups. This outcome warrants larger clinical trials to explore the potentials of these safe food supplements in the prevention and prophylaxis of diseases due to dysregulated metabolism, such as fatty liver disease, and infections such as COVID-19 in which balanced immunomodulation are of utmost importance, besides their administration as an adjunct to existing therapeutic approaches of both communicable and non-communicable diseases. [Display omitted]